The Cost of Financial Regulation in The United States of America: A Study of Operational Impact on Banks - Ngo, Kevin Stefan (2013)
The banking system in the United States of American is a critical element of world economy. History has shown that if U.S. banks were left to their own devices the result would be turmoil in the global marketplace. Politicians, businesses, consumers and society as a whole agree that some system of checks and balances in the form of regulation is required to subdue a bank’s profit maximize motivates. This paper examines the relationship between the cost of regulatory compliance and a bank’s operating functions by providing empirical evidence through both traditional and non‐traditional approaches. Each approach gathers data from publically available 10‐K Annual disclosures and regulatory financial reports to determine if and how a bank holding company’s operating functions are affected by regulatory shocks in the form of Dodd–Frank Wall Street Reform and Consumer Protection Act rulings and to a lesser extent the Basel Accords. The study focuses primarily on the periods between 2007 to 2012, which coincide with the period leading up to the 2008 Global Financial Crisis and the subsequent actions by the U.S. government to prevent future crises through the passing of Dodd‐Frank into law on July 12th, 2010.